Examining the Implementation of PSAK 109 on Financial Reporting for Zakat, Infak, and Sedekah Accounting at BAZNAS/LAZIS DKI Jakarta - Ridho, Ali; Ridho, Dewinta Illinia (LITERATUS, 2024)
The realization of zakat, infaq and sedekah (ZIS) collection in Indonesia is still relatively low compared to its potential, the main causal factor is the low level of public trust in ZIS management organizations. The implementation of PSAK 109 in ZIS management organizations can improve accountability, transparency, and public trust. The purpose of this study is to analyze the financial statements of zakat, infaq and sedekah management at BAZNAS DKI Jakarta, so that it can be seen how the financial statements of BAZNAS DKI Jakarta are recorded, and to assess the extent to which the accounting process of its financial statements is in accordance with PSAK 109. This study involves qualitative research methodology, and is descriptive in nature which is conducted by observing data on the financial statements of BAZNAS DKI Jakarta and direct interviews with the leaders of BAZNAS DKI Jakarta. Based on the existing indicators and the analysis conducted, the results of this study indicate that the accounting process carried out starting from the process of recognition, measurement, presentation and disclosure is in accordance with PSAK 109. In the presentation in the form of financial reports in the form of financial position reports, fund change reports, cash flow reports, and notes to the financial reports prepared by BAZNAS DKI Jakarta, it is in accordance with PSAK No. 109 concerning accounting for zakat, infak and sedekah.